Inovasi Tissue Engineering Menggunakan Limbah Ikan Sebagai Biomaterial Pengisi Soket Pasca Ekstraksi - Hendri Jaya Permana; Fatkhur Rizqi; Ade Ivin Defrigunawan (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Paradigm changes from replacement tissues into regenerating strengthened and start developed in dentistry. Tissue engineering in dentistry was developed such as material filler post extraction socket. The opened socket post extraction very range against contamination and infection. The current substances filler socket post extraction still not available. On the other hand, as maritime country Indonesia potentially in fisheries. The problem is the end of fish processing being fish waste, consisting of scales, spines, and fins. Fish waste is still underutilized. This study is study literature to discussing tissue engineering using fish waste as biomaterial filler post-extraction socket. Fish waste containing calcium, chitin, collagen, steroid, saponins, alkaloids, phenolics hydroquinones, and ninhidrin. That content is similar to bones, especially in the alveolar bone. Khitosan as the main derivatives of chitin is suspected play role in stimulating osteoblast activity as cell bone formed. Alkaloids, steroid, saponins, and phenolics hydroquinones are able to modulate activity of immune cells and antimicrobial. Based on the above analysis, it can be inferred that the fish waste is potentially as biomaterial socket filler based tissue engineering because it can stimulate regeneration of alveolar bone and antimicrobial.